Heavy metal concentration in muscle of pike (Esox lucius Linnaeus, 1758) from Anzali international wetland, southwest of the Caspian Sea and their consumption risk assessment. (1st October 2016) - Adel, Milad; Dadar, Maryam; Fakhri, Yadolah; Oliveri Conti, Gea; Ferrante, Margherita
Abstract: This study evaluated the concentrations of nine heavy metals in muscle specimens of pike ( Esox lucius Linnaeus, 1758) from four sites of southwest of the Caspian Sea: Shijan, Abkenar, Hendakhale and Siakeshim. The potential human health risks due to consumption of pike have been assessed by estimated average daily intake (EDI) and target hazard quotient (THQ) of metals. In particular, Cu, Zn, Cd, Pb, Hg, As, Ni, Co and Mn were quantified in the edible tissue of specimens by AAS determination. The average metal concentrations of Cu, Zn, Cd, Pb, Hg, As, Ni, Co and Mn measured in this study were 1.12 ± 0.264, 5.37 ± 0.702, 0.058 ± 0.023, 0.20 ± 0.035, 0.005 ± 0.002, 0.17 ± 0.047, 0.33 ± 0.062, 0.28 ± 0.034 and 0.20 ± 0.035 μg/g w wt, respectively. Our results demonstrate the consumption of muscle of pike for adult and children as less than 1, hence residents of these regions will not be exposed to significant health risks.